Growing Cities, Growing Conflicts: Urbanisation and Socioeconomic Influences on Land Issues in Dodoma, Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Rapid urbanisation, population growth and deepening socioeconomic inequalities in Dodoma City, Tanzania, are triggering pervasive land conflicts that obstruct sustainable development. Rapid urbanisation in developing countries has heightened land competition, exposing underlying socioeconomic inequalities and governance issues. In sub-Saharan Africa, cities are expanding faster than institutions can manage land access, tenure security, and urban planning. Tanzania’s capital, Dodoma, illustrates these trends, where population growth, poverty, and unregulated urban sprawl frequently lead to disputes over ownership, compensation, and land use. This study explores the link between urban growth, poverty, and land conflicts in Dodoma, Tanzania. Using an explanatory sequential mixed-methods approach, data were gathered from 258 households via stratified random sampling, along with 12 key informant interviews with planners, surveyors, and land officers. Quantitative analysis employed multiple linear regression, complemented by qualitative insights to provide context. Findings reveal that socioeconomic factors such as education and employment significantly impact land conflicts, while population growth, migration, and informal settlements contribute to disputes through unplanned expansion. Applying Resource Dependence Theory and Urbanisation Theory reveals that conflicts stem not only from resource scarcity but also from structural inequalities that impede fair access to land amid rapid urbanisation. The study suggests that effective conflict mitigation requires integrated strategies combining poverty alleviation, legal empowerment, and participatory urban planning. Strengthening land governance and fostering inclusive development are essential for a sustainable and peaceful urban transformation in Tanzania and comparable regions.